Horizontal Transmission of Intracellular Insect Symbionts via Plants - Chrostek, Ewa; Pelz-Stelinski, Kirsten; Hurst, Gregory D. D.; Hughes, Grant L. (Frontiers in Microbiology, 2017)
Experimental evidence is accumulating that endosymbionts of phytophagous insects may transmit horizontally via plants. Intracellular symbionts known for manipulating insect reproduction and altering fitness (Rickettsia, Cardinium, Wolbachia and BEV) have been found to travel from infected insects into plants. Other insects, either of the same or different species, can acquire the symbiont from the plant through feeding, and in some cases transfer it to their progeny. These reports prompt many questions regarding how intracellular insect symbionts are delivered to plants and how they affect them. Are symbionts passively transported along the insect-plant-insect path, or do they actively participate in the process? How widespread are these interactions? How does symbiont presence influence the plant? And what conditions are required for the new infection to establish in an insect? From an ecological, evolutionary and applied perspective, this mode of horizontal transmission could have profound implications if occurring frequently enough or if new stable symbiont infections are established. Transmission of symbionts through plants likely represents an underappreciated means of infection, both in terms of symbiont epidemiology and the movement of symbionts to new host species.